2021
DOI: 10.1371/journal.pone.0248654
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of biogas production from tomato bio-waste in mesophilic batch and continuous anaerobic digestion systems

Abstract: Annually, agricultural activity produces an enormous amount of plant biomass by-product. Many studies have reported the biomethane potential of agro-industrial wastes, but only a few studies have investigated applying the substrates in both batch and continuous mode. Tomato is one of the most popular vegetables globally; its processing releases a substantial amount of by-product, such as stems and leaves. This study examined the BMP of tomato plant (Solanum lycopersicum Mill. L. cv. Alfred) waste. A comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The experimental methane yield obtained in reactor 8 is almost indistinguishable from the reported values during AcoD of food wastes and heterogenous straws (maize, sorgos, and wheat). The study reported a maximum methane yield of 392 mL/g VS at food wastes to the straw mixing ratio of 5:1 at 35 • C (Yong et al, 2015) and higher than the values of 289 mL/g VS was reported during AcoD of tomato plant waste and corn stover at a ratio of 7:3 on VS and C/N ratio basis (Szilágyi et al, 2021). The studies cited that properly utilizing the released VFAs during the co-digestion resulted in increased methane yield under mesophilic conditions.…”
Section: Biogas Biomethane Production and Kineticsmentioning
confidence: 57%
“…The experimental methane yield obtained in reactor 8 is almost indistinguishable from the reported values during AcoD of food wastes and heterogenous straws (maize, sorgos, and wheat). The study reported a maximum methane yield of 392 mL/g VS at food wastes to the straw mixing ratio of 5:1 at 35 • C (Yong et al, 2015) and higher than the values of 289 mL/g VS was reported during AcoD of tomato plant waste and corn stover at a ratio of 7:3 on VS and C/N ratio basis (Szilágyi et al, 2021). The studies cited that properly utilizing the released VFAs during the co-digestion resulted in increased methane yield under mesophilic conditions.…”
Section: Biogas Biomethane Production and Kineticsmentioning
confidence: 57%
“…after removal of particles larger than 2 mm) was used for BMP measurement. A detailed description of the gas sampling and measurement procedures can be found in Szilágyi et al 2021 [35].…”
Section: Determination Of Ad Chemical Parametersmentioning
confidence: 99%
“…Essential needs for the development of strategies for the management of solid waste include information on the types of wastes, as well as their composition, physical and chemical features, and the amounts of trash that are produced [19,20]. In order to effectively manage solid waste, it is required to investigate the characteristics of the waste material, in addition to determining where the trash came from.…”
Section: Data Collection and Analysismentioning
confidence: 99%